PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR PADA MATERI ARITMATIKA SOSIAL DIKELAS VII MTs SWASTA TAMAN PENDIDIKAN ISLAM (TPI) SAWIT SEBERANG TAHUN PELAJARAN 2017/2018 - Nurul Alpristari Gisty; Mara Samin Lubis (AXIOM : Jurnal Pendidikan dan Matematika, 2018)
Research this aim for find out: is there is influence positive betweenapproach CTL learning against results learn student class VII MTsSTaman Pendidikan Islam (TPI) Sawit Seberang Year 2017/2018lesson. Research this is research quantitative. Population researchthis is all over student class VII Taman Pendidikan Islam (TPI)Sawit Seberang the numbering 184 students. Sample in research thisis number VII-1 number 40 students as class experiment and classVII-2 numbered 40 students as class control. Findings in researchthis show: there is influence approach CTL learning against resultslearn mathematics student class VII MTsS Taman Pendidikan Islam(TPI) Sawit Seberang. This based on calculation: (1) Score resultslearn classes taught strategy CTL learning obtain 3425 and anaverage of 85.63 while classes taught strategy learning conventionalobtained 3185 and an average of 79.63 (2) statistics test t obtainednumber amounting to 2,564 while t- table amounting to 1,9908. Withthereby means there is a positive effect between strategy CTLlearning to results learn student mathematics.